التسويق الإلكتروني بين الضوابط الشرعية والآثار الاقتصادية - صفاء, حشيفه (University of Eloued جامعة الوادي, 2019)
تناولت في هذه المذكرة موضوع من المواضيع المهمة في عالم المعاملات المالية المعاصرة ألا وهو التسويق الإلكتروني، حيث عنونتها بـــــ: التسويق الإلكتروني بين الضوابط الشرعية والآثار الاقتصادية"، وقد دارت إشكاليتها حول: أثر تطبيق الضوابط الشرعية للتسويق الإلكتروني على الاقتصاد، وقد عولجت هذه الأخيرة في مقدمة وثلاث مباحث وخاتمة؛ ففي المقدمة ذكرت عناصرها بالتفصيل؛ بعدها تطرقت إلى المبحث الأول، الذي خصصت فيه الكلام عن التسويق الإلكتروني وما يتعلق به من مصطلحات وعناصر وأنواع، ثم تطرقت إلى المبحث الثاني الذي تكلمت فيه عن الضوابط الشرعية للتسويق الإلكتروني من خلال التكييف الفقهي لهذه المعاملة والضوابط الشرعية للعمليات المتعلقة به، وختمت هذا المبحث بالضوابط الشرعية للترويج الإلكتروني لأنه هو الأساس في التسويق، ثم انتقلت إلى مبحث ثالث: بينت فيه مدى تحقيق الآثار الاقتصادية للتسويق الإلكتروني في ظل تطبيق أحكام الشريعة الإسلامية من خلال استبيان وزعته على عدد معين من المؤسسات الاقتصادية، وفي الأخير ختمت هذه الدراسة بخاتمة حوت أهم النتائج والتي من أهمها: عدم الالتزام ببعض الضوابط الشرعية للتسويق الإلكتروني لم يؤثر اقتصاديا على نمو وتطور المؤسسات الاقتصادية ثم ذكرت أهم التوصيات والتي من بينها: على المؤسسات الاقتصادية تحري الحلال الطيب في جميع العمليات التسويقية. "In this dissertation, I discussed a number of important topics in the world of contemporary financial transactions, namely the electronic marketing. It is entitled “the electronic marketing between the legitimate regulations and economic effects"". The problematic revolved about the impact of applying the Islamic rulings over the electronic marketing on the economy. The work consists of an introduction, three chapters and a conclusion. The introduction included all details about the studied elements. The first chapter was devoted to talk about electronic marketing and related terms, elements and types; the second was about the legitimate regulations of the electronic marketing through the adaptation of the jurisprudence treatment and the legal controls of the processes related to it. The chapter concluded with the legal controls of the electronic promotion because it is the basis in marketing. The third chapter showed the extent of achieving the economic effects of electronic marketing in the application of the provisions of Islamic law through a questionnaire distributed to a certain number of economic institutions. Finally, this study concludes with the most important findings of the study. The lack of adherence to certain religious rules for electronic marketing has not affected the economic growth and development of economic institutions. Then I mentioned the most important recommendations like advising the economic institutions to look for and work within the good Halal in all marketing processes. "
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: التسويق الإلكتروني؛ الضوابط الشرعية؛ الآثار الاقتصادية؛ المؤسسات الاقتصادية.; electronic marketing; religious regulations; economic impacts; economic institutions.